The significance of the local trade in natural resource products for livelihoods and poverty alleviation in South Africa - Shackleton, Sheona E (Rhodes University, Faculty of Science, Department of Environmental Science, 2006)
What role can the commercialisation of natural resource products play in the efforts to reduce poverty and vulnerability and how can this be enhanced? With poverty alleviation at the top of the global development agenda, this is a question posed by many scholars, practitioners, donor agencies and government departments operating at the environment-development interface. However, recent commentary on this issue is mixed and ambiguous, with some observers being quite optimistic regarding the potential of these products, while others hold a counter view. This thesis explores the livelihood contributions and poverty alleviation potential of four products traded locally in the Bushbuckridge municipality, South Africa; namely traditional brooms, reed mats, woodcraft and a beer made from the fruits of Sclerocarya birrea. A common approach, employing both quantitative and qualitative methods, was used to investigate the harvesting, processing and marketing arrangements, sustainability and livelihood contributions of each product. The results illustrate that any inference regarding the potential of the trade to alleviate poverty depends on how poverty is defined and interpreted, and on whether the role of these products is assessed from a holistic livelihood perspective that includes notions of vulnerability, alternatives and choice, diversification and the needs of rural producers themselves. Overall, the products studied were key in enhancing the livelihood security of the poorest members of society, forming an important safety net and assisting in raising household incomes to levels equivalent to the wider population, but generally were unlikely, on their own, to provide a route out of poverty. However, there were notable exceptions, with marked variation evident both within and across products. Incomes often surpassed local wage rates, and a minority of producers were obtaining returns equivalent to or greater than the official minimum wage. Other benefits, such as the opportunity to work from home or to diversify the livelihood portfolio, were also crucial, with the trade representing different livelihood strategies for different households. When viewed within the context of rising unemployment and HIV/AIDS these findings assume greater significance. While the trades were complex and growth limited, livelihood benefits could be improved on a sustainable basis if the sector was given the attention and support it deserves.
Keywords: Poverty -- South Africa; Rural poor -- South Africa; Natural resources -- South Africa; Selling; Handicraft -- South Africa -- Commerce